Analisis Dan Perancangan Sistem Pendukung Keputusan Pemilihan Smartphone Gaming Menggunakan Metode AHP - Christian, Christian; Roestam, Rusdianto (LPPM Universitas Dinamika Bangsa, 2021)
The rapid development of information technology now is strongly opposed to the development of smartphones with a variety of services offered by well-known companies of all brands with the latest features, various specifications, communication tools to the internet. The purpose of this study is to analyze and design a decision support system for smartphone gaming selection using the AHP (Analytical Hierarchy Process) as a decision support method, modeling system using UML (Unified Modeling Language) consisting of Use Case Diagrams and Activity Diagrams, with prototype as a design. This study produced a prototype of a gaming phone decision support system that can manage computerized gaming phone data and can present a ranking report on gaming phone criteria.